Presurgical Aspects of Nutrition in Tuberculous Spondylitis Patients - Farid Yudoyono; Rully H. Dahlan; Muhammad Z. Arifin; Achmad Adam (Universitas Kristen Maranatha, 2018)
Tuberculous spondylitis is a chronic infectious disease caused by Mycobacteriumtuberculosis on the vertebral bone. Involved less than 3% of all cases of TB, but the incidencevaries around the world, and is associated with the quality of public health and socioeconomicconditions.The purpose of this study is to investigate the presurgical aspects of nutrition inpatients with tuberculous spondylitis. A total of 39 consecutive patients between January 2011-December 2012 were evaluated retrospectively. All patients diagnosed with spondylitistuberculousis and treated with decompression, stabilization and fusion. All patients had beendiagnosed with Spondylitis tuberculousis based on history taking, physical examination,laboratory finding and MRI. Our study showed that of all subjects, ten male patients and eightfemale patients had cervical (n=1), thoracic (n=15), and lumbar (n=2) tuberculousspondylitis.The average age of the patients was 32.83 ± 12.25 (17-56) years old. The averagepreoperative body mass index (BMI) was 16.67 ± 1.2 kg / m2, albumin levels 3.23 ± 0.21 g / dl,total protein level 6.2 ± 0.34 g/dL. These were lower than normal value. We conclude thattuberculous spondylitis patients experience nutritional deficiencies presurgically andnutritional support should be considered pre-operatively.Keywords: Mycobacterium tuberculosis, nutritional state, presurgical aspect,tuberculousspondylitis